Incidence, treatment, and outcomes of primary and recurrent Non-Wilms renal tumors in children: Report of 109 patients treated at a single institution. Issue 4 (August 2020) - Qureshi, Sajid S.; Bhagat, Monica; Verma, Kamlesh; Yadav, Subhash; Prasad, Maya; Vora, Tushar; Chinnaswamy, Girish; Amin, Nayana; Smriti, Vasundhara; Baheti, Akshay; Laskar, Siddharth; Khanna, Nehal; et al.
Summary: Introduction: Non-Wilms renal tumors represent a compelling subset of childhood renal tumors. However, their relative rarity renders accurate diagnosis, and therapy challenging which in some instance is inferred from their adult counterparts. Objective: To describe the incidence and analyze the diagnostic challenges, therapies and, outcomes of non-Wilms renal tumors at the largest tertiary cancer centre in India. Methods: All patients with histologically confirmed non-Wilms renal tumours diagnosed in the paediatric oncology unit of Tata Memorial Hospital between 2006 and 2019 were included. Data regarding clinical and radiological features and treatment outcomes were retrieved from the prospectively maintained institutional database. At the outset, histological types were categorised into a high and low-risk group depending on anticipated survival. Survival analysis was performed utilising the Kaplan–Meier method on SPSS software version 24.0. Results: Of the 569 patients with renal tumors, 109 (19%) patients with primary (n = 97) or recurrent ( n  = 12) non-Wilms renal tumors were included. Histological high-risk group included clear cell sarcoma (CCSK) (39.4%), renal cell carcinoma (RCC) (19.3%), malignant rhabdoid tumor (MRTK) (12.8%), Ewing's sarcoma (rES) (15.6%), synovial sarcoma (2%), and undifferentiated sarcoma (2%). The low-risk group comprised of congenital mesoblastic nephroma (CMN) (4.6%), cystic partially differentiated nephroblastoma (2%), and other rare tumors (3%). Diagnostic error occurred in 2 patients in the high-risk group. All low-risk tumours were treated with surgery alone and most (97%) high-risk tumors were operated either upfront (61.5%) or after preoperative chemotherapy (38.4%). Adjuvant therapy based on histology was offered to 70%. The recurrent tumors received various salvage treatments including chemotherapy; radiotherapy; surgery and immunotherapy, however, only 2 patients could be salvaged. The 3-year overall survival for the entire cohort with primary tumors was 59%, and the survival rates were 76.7%, 77.9%, 0.0%, and 52% for CCSK, RCC, MRTK, and rES (summary figure). Low-risk tumors had 100% survival while the recurrent tumors had a median survival of 10.5 months. Conclusions: Non-Wilms renal tumors constitute a heterogeneous group of tumors, accounting for less than 20% of all renal tumors. Low-risk tumors are associated with excellent outcomes following surgery alone while the high-risk tumours have a variable outcome. MRTK and recurrent non-Wilms tumour have the worst survival. Favourable outcomes for CCSK and RCC and worst outcomes for MRTK were observed in this study. Renal ES have higher incidence of treatment failure and unsatisfactory outcomes. Recurrent non-Wilms tumours have an extremely poor outcome and more alternative or innovative approaches are needed for their treatment.